NILAI BUDI DAN KEISLAMAN DALAM PANTUN MELAYU PONTIANAK - Abdurahraman Abror (The Pontianak State Institute of Islamic Studies, 2011)
This writing discusses the local wisdom of the Malay community of Pontianak found in pantun (Malay traditional poetry). As an original literature of the Malay community, pantun not only serves as an artistic expression but it also contains glorious values. The writer thinks that pantun serves as a medium of transition of values from one generation to the next. There are various values found in the pantun of the Pontianak community such as belief, relationship between fellow humans, and relationship between humans and environment.